The associations between some biological markers, obesity, and cardiovascular risk in Slovenian children and adolescents - Nataša Marčun Varda; Martina Medved; Laura Ojsteršek (BMC, 2020)
Abstract Introduction The occurrence of cardiovascular diseases and metabolic disorders steadily increases with the body mass index (BMI). Since the latter is not the best and earliest indicator of obesity and cardiovascular risk, the aim of the study was to evaluate some potential biological markers that would allow us to detect children and adolescents at higher risk at an early stage. Methods A sample of 330 children and adolescents were included in the study and divided into four groups: obese patients with hypertension, normal-weight patients with hypertension, patients with mildly elevated lipids and a control group of healthy children and adolescents. Some clinical parameters (age, body weight, body height, BMI, waist circumference, hip circumference, blood pressure), biochemical parameters (glucose, total cholesterol, triglycerides, HDL, LDL, apolipoprotein A1, homocysteine) and biological markers of obesity (ghrelin, adiponectin, leptin) were evaluated. Results Ghrelin and adiponectin were found to have a strong negative statistically significant correlation with BMI in all three observed groups (p < 0.001), but not in the control group (p = 0.053 and p = 0.316, respectively). In addition, leptin had a strong positive statistically significant correlation with BMI in all four groups (p < 0.001 for the research groups, p = 0.009 for the controls). In the group of obese patients with hypertension, statistically significant differences in all three markers of obesity were found in comparison to the control group (p < 0.001 for all markers). In the group of patients with mildly elevated lipids, ghrelin and leptin were significantly different (p = 0.002 and p < 0.001, respectively). In the group of normal-weight hypertensive patients, only values of ghrelin were different compared to the control group (p = 0.001). Conclusion In the research groups, significant differences were found in clinical, biochemical and biological parameters compared to the control group. The observed biological markers of obesity are useful early markers for identifying groups of patients that are at cardiovascular risk.